The white clouds doesn’t melt into thin air: An anti-racist vision of digital colonialism - Gregório Santos, Taynara (2024)
The book presents the concept of digital colonialism in a dual dimension: subjective and objective. Subjective, because by addressing the aspect of the formal subsumption of production and consumption processes, it highlights that cognition, knowledge, and social behavior are constituted through the mediation of racist algorithms, present in the entirety of social relations. Objective, because it shows that this process depends on the exploitation of natural resources in territories of the Global South, which renews racism and racialization. Written with the authors' experience in popular education, the book flows with a clarity that facilitates understanding. By combining concepts from historical and dialectical materialism and anticolonial literature, the study offers a broad and rich discussion on digital colonialism and how we can confront it.